La dimensione relazionale nei siti web delle agenzie di viaggio on-line - Cioppi, Marco; Buratti, Andrea (Piccola Impresa / Small Business, 2014)
The article deals with the design of the websites of travel agencies online, identifying the main variables appropriately summarized in a few key dimensions. The results show the importance of the relational dimension to the websites of travel agencies online the relevance of which is neglected by many existing models in the literature. The results show some managerial implications addressed to the leaders of the websites of travel agencies online.